Cost Pool Classification and Judgment Performance - Mastilak, M. Christian (The Accounting Review, 2011)
ABSTRACT Managers must understand relations among costs in order to make decisions. Prior literature assumes managers' use of cost accounting system output is affected by the information coming from the system, but not by the design of the cost system itself. This study examines how the classification of costs into cost pools affects the accuracy of individuals' understanding of relations among costs. I hypothesize that individuals will estimate relations between costs in the same cost pool first and thus more accurately than relations across different pools, because cost pools provide strong cues that meaningful relations are likely to exist within, but not across, pools. I also hypothesize that cost location (within- versus across-pool) has a greater effect on individuals' judgment accuracy when relations among costs are negative than when they are positive. Experimental results are generally consistent with these hypotheses. This experiment shows that cost pool classification choices not only affect the information managers receive, but also their interpretation and use of that information. Data Availability: Contact the author.